“Herstory” in Twenty-First Century Indian English Children’s Literature: Subverting Gender Binaries in Mayil Will Not Be Quiet! and Queen of Ice - Chanda, Anurima (SARE: Southeast Asian Review of English, 2018)
In the last two decades, there has been a new turn in Indian English children’s literature that seeks to move beyond a didactic and moralistic setup within a homogenised culture to a more plural context where marginal voices can be represented sensitively without being sensationalised. Within this articulation, conventional gender roles have been challenged targetting female characters who resist simplistic gender binaries. Through a close reading of two texts – Mayil Will Not Be Quiet! (2011) and Queen of Ice (2014) – this article attempts to explore this shift in twenty-first century Indian English children’s literature. It will argue that by privileging the very voices that were excluded from previous Indian English children’s literature, these texts subvert the traditional gender roles and expectations that have remained such a dominant feature of this genre.